Analysis of microbial components of two-liquid phase bioreactors for improved volatile organic compund biofiltration - Ng, Chow Goon (2014)
The dynamics of the microbial communities in a two-liquid phase partitioning bioreactors (TPPBs) for treatment of volatile organic compounds (VOCs) was investigated. The TPPBs were set up in 0.5 L stirred reactors using silicone oil (at 10% v/v) as the non-aqueous liquid (NAL) phase and hexane as the model VOC, which also served as the sole carbon source in the environment of mineral salt medium (MSM). These TPPBs showed better microbial growth, higher biosurfactant production and greater efficiency in hexane removal compared to the conventional monophasic bioreactors (MPBs) over the 52 weeks of study. Properties such as rate of community change, microbial diversity richness and the dominance of certain bacterial groups showed some degree of similarity when the two types of bioreactors were compared, but the actual microbial compositions between TPPBs and MPBs revealed differences across time as analyzed by a strategy combining 16S rDNA sequencing with PCR-amplified ribosomal DNA restriction analysis (ARDRA), phylogenetic analysis and DGGE. The approach also allowed us to distinguish the culturable isolates from the bioreactors and the clones from the 0th week community’s full-length 16S rDNA library, down to the genus level. This was mapped to the DGGE profiles to derive the community structures based on key genera over time. Dominant subpopulations with a biased presence in one type of bioreactor or other were identified. It was revealed that TPPBs supported a higher abundance of Mycobacterium while the MPBs supported more Rhodococcus across time. Monoculture study of the isolates were able to verify their intrinsic hexane catabolic capacity and growth on hexane. The association between each strain’s level of growth on hexane, cell surface hydrophobicity and biosurfactant production were examined with respect to the influence of the NAL phase, and five functional Groups each defined by a profile of these properties were derived. Interestingly, a highly similar distribution of these five Groups across both types of bioreactors and all time surfaced, implying distinct advantages associated with this functional group distribution. A hexane uptake scenario involving bacterial interactions within a microbial community carrying the five functional Groups of bacteria in the monophasic and biphasic contexts will be discussed.